Analgesic requirement in first 24 hours following Total Knee Arthroplasty with or without Peri-articular Levobupivacaine Infiltration - Memon AR; Gul R (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2019)
Introduction: Post-operative analgesia is an important part of Total Knee Arthroplasty (TKA) to facilitate early mobilization and patient satisfaction. We investigated the effect of periarticular infiltration of the joint with levobupivacaine local anesthetic (LA) on the requirement of analgesics in the first 24 hours period post operatively.  Methods: 28 patients who underwent TKA were analysed retrospectively. They were divided into two groups of 14 each; who did and did not receive the LA infiltration respectively. Analgesic requirement was assessed in terms of the amount of paracetamol, morphine, diclofenac, oxynorm and tramadol administered in 24hrs post operatively. Visual analogue scale was used to record the subjective pain intensity.  Results: There was significant reduction in consumption of morphine in patients receiving LA infiltration (p-0.03). The amount of tramadol and oxynorm was also halved in LA infiltrated group although the requirement of paracetamol remained the same. LA infiltrated group received almost 1.5 times more diclofenac as compared to the non-infiltrated group. Visual analogue pain scale revealed significant reduction in pain scores in LA infiltration group at 6 and 12 hours (p=0.002).  Conclusion: Intraoperative LA infiltration provides better analgesia and greater patient satisfaction after TKA.